Dentoskeletal Effects of Modern Hybrid Fixed Functional Appliances - Lam, Alexander Khoi-Nguyen Thanh; Schmid, Jonas Quirin (Archive of Orofacial Data Science, 2024)
AIM: This study performs an in-depth analysis of the literature to evaluate the dentoalveolar and skeletal effects of modern hybrid fixed functional appliances (HFFAs). METHODS: An extensive literature search spanning from January 2010 to November 2023 was executed across three databases: PubMed, Cochrane Library, and Google Scholar. Additionally, a manual search was done by employing the names of relevant authors and screening the references within the included articles. The assessment for eligibility was based on the PICO approach: (P)articipants: Any patients exhibiting Class II division 1 malocclusion up to the age of 18; (I)ntervention: Treatment with HFFAs; (C)omparison: Untreated individuals; (O)utcome measures: (a) Amount of overjet reduction; (b) Changes in upper and lower incisor proclination/protrusion; (c) Skeletal maxillary/mandibular alterations (ANB, SNA, SNB values); (d) Mandibular growth (changes in mandibular length); and (e) Treatment duration. RESULTS: Nine clinical trials were included in this study, representing a total of 584 adolescents with Class II division 1 malocclusion. Cephalometric measurements indicate pronounced dentoalveolar effects, including lower incisor proclination and upper incisor retroclination, to correct overjet and overbite. Skeletal effects, such as modest maxillary restriction and improvement in the maxillary-mandibular anteroposterior relationship, were less prominent. CONCLUSION: Although successful at Class II dental malocclusion correction, HFFAs induce unwanted side effects such as significant lower incisor proclination and clockwise rotation of the occlusal plane. Further research, particularly focusing on HFFAs coupled with skeletal anchorage, is necessary.